2003
DOI: 10.1385/abab:106:1-3:383
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Rheological Properties of Corn Stover Suspensions

Abstract: Corn stover is currently being evaluated as a feedstock for ethanol production. The corn stover suspensions fed to reactors typically range between 10 and 40% solids. To simulate and design bioreactors for processing highly loaded corn stover suspensions, the rheologic properties of the suspension must be measured. In systems with suspended solids, rheologic measurements are difficult to perform owing to settling in the measurement devices. In this study, viscosities of corn stover suspensions were measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 8 publications
3
22
0
Order By: Relevance
“…We have previously found torque rheometry to be an effective method for characterizing the rheological behavior of highly viscous wood fiber suspensions for extrusion [16][17][18]. For the corn stover studied here, the steady-state rheological properties are well described by the Bingham model, with a yield stress that increases with solids concentration, consistent with that reported by Pimenova and Hanley [12,13] and Viamajala et al [14]. However, yield stress values reported here are significantly larger than those reported by Pimenova and Hanley and Viamajala et al This difference is attributed in part to larger particle sizes employed in the present study.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…We have previously found torque rheometry to be an effective method for characterizing the rheological behavior of highly viscous wood fiber suspensions for extrusion [16][17][18]. For the corn stover studied here, the steady-state rheological properties are well described by the Bingham model, with a yield stress that increases with solids concentration, consistent with that reported by Pimenova and Hanley [12,13] and Viamajala et al [14]. However, yield stress values reported here are significantly larger than those reported by Pimenova and Hanley and Viamajala et al This difference is attributed in part to larger particle sizes employed in the present study.…”
supporting
confidence: 86%
“…Thus, by fitting the above model for the predicted torque to experimental torque-rotation rate data, the yield stress and plastic viscosity can be extracted. For this fitting procedure, we employ a Gauss-Newton method to minimize the error between the measured and predicted torques [12]. We note that Eqs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing insoluble solids, the viscosity of the slurry increases sharply, and viscosity for pretreated corn stover (PCS) solids has been shown to be highly non-Newtonian [13]. Preliminary work in our laboratory has shown that approximately 12-15% insoluble solids represents the upper limit at which slurries of unhydrolyzed PCS solids can be mixed effectively in stirred tank reactors (STRs).…”
Section: Introductionmentioning
confidence: 99%
“…To simulate the flow of cellulosic slurries in stirred tanks, the rheological properties of these suspensions must be known. This high-solids slurry definition can be regarded as the solids region where the slurry viscosity is highly non-Newtonian at approximately 12 to 15% insoluble solids [7]. High-solids slurries such as corn stover typically range from 10 to 40% solids [8].…”
Section: Introductionmentioning
confidence: 99%